KEPENTINGAN INDONESIA MELAKUKAN IMPOR KEDELAI DARI MALAYSIA - Yurika, Dhea; Retnaningsih, Umi O. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Indonesia and Malaysia has a long relationship politically, economically, and culturally. Soybean import from the United States decreased while from Malaysia increased in 2012-2016. This research described reasons of Indonesia to do import from Malaysia than from the other countries.This qualitative research inquired the interests of both countries to strengthen economic relationship for import-export. To answer the phenomena data from books, journals, news from newspapers, and official documents from Indonesian Trade Ministry was utilized. Economic theory of liberalism from John Stuart Milland and Jean Jacques Rousseau help researcher in analysing the data.The research showed that Malaysian soybean is competitive in terms of price and quality. Stable soybean supply in Malaysia to Indonesian products for tofu, soya bean, ketchup, and any other foods could improve cooperation between the two countries. In addition political and cultural tied on D-8, Organization of Islamic Conference, and Non-Aligned Movement can tighten cooperation in soybean import. Â Keywords: Importance, Import, Soybean, PartnershipÂ